MANAJEMEN SEKOLAH DALAM IMPLEMENTASI PENGELOLAAN KINERJA DI PLATFORM MERDEKA MENGAJAR: STUDI KASUS GURU DAN KEPALA SEKOLAH JENJANG SEKOLAH DASAR DI KECAMATAN SILUQ NGURAI - Nurul Chasanah; Agus Dedi, Novi Justica Rofiyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ASN Performance Management on the Merdeka Mengajar Platform is a tool that makes it easier for teachers and principals to determine more contextual performance targets according to education unit reports and career development. The West Kutai district government uses performance management data as the basis for payment of Additional Employee Income (TPP) for ASN teachers and principals, therefore ASN teachers and principals are required to carry out PMM performance management that is integrated with BKN's ekinerja.The purpose of this study is how the implementation of PMM performance management at the Elementary School level in Siluq Ngurai District is applied? What are the inhibiting factors and how is the implementation of school management in overcoming these obstacles. This research method uses qualitative descriptive research with case studies of teachers and principals. The location of the study was at the elementary school level in Siluq Ngurai District, West Kutai Regency. Data analysis was carried out by data reduction, data presentation and drawing conclusions.The conclusion of this study is that all ASN teachers and school principals in West Kutai Regency have used Performance Management on the Merdeka Mengajar Platform application, but there are still several obstacles, namely: 1) Limited internet access 2) Lack of training and mentoring, 3) Lack of devices that support learning 4) Lack of motivation of teachers and principals in using technology. Based on the results of interviews with supervisors, teachers and principals, the suggestions made to overcome these obstacles are as follows: 1) Collaborate with the village government to procure starlink at schools at a cost that is affordable for schools. 2) Create branches of learning communities with nearby schools so that training can be maximized and effective. and ask for regular assistance. 3) The need for budgeting for learning media that can support teachers in the teaching and learning process in the classroom based on the results of data-based education reports. 4) To overcome the lack of motivation of teachers and principals in using technology, a personal approach is carried out, providing motivation and training or direct practice periodically.